Use of Glucose Oxidase Immobilized on Magnetic Chitosan Nanoparticles in Probiotic Drinking Yogurt - Afjeh, Maryam Ein Ali (Food Sci Anim Resour, 2019)
The aim of this study was to investigate the effect of glucose oxidase (GOX) immobilized on magnetic chitosan nanoparticles (MCNP) on the viability of probiotic bacteria and the physico-chemical properties of drinking yogurt. Different concentrations (0, 250, and 500 mg/kg) of free and immobilized GOX were used in probiotic drinking yogurt samples. The samples were stored at 4°C for 21 d. During storage, reduction of the number of probiotic bacteria in the samples with enzyme was lower than the control sample (without enzyme). The sample containing 500 mg/kg immobilized enzyme had the highest number of Bifidobacterium lactis and Lactobacillus acidophilus. The samples containing immobilized enzyme had lower acidity than other samples. Moreover, moderate proteolytic activity and enough contents of flavor compounds were observed in these samples. It can be concluded that use of immobilized GOX is economically more feasible because of improving the viability of probiotic bacteria and the physico-chemical characteristics of drinking yogurt.